Pemanfaatan Media Pembelajaran Berbasis AI untuk Mendukung Education for Sustainable Development (ESD) di Madura: Pendekatan Kontekstual Berbasis Kearifan Lokal - Moh Khalid Hasan; Hesti Kusumawati; Abdul Wafi; Aldi Firnanda; Sahril Hamdani (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study was motivated by the limited use of technology in learning that supports Education for Sustainable Development (ESD) in Madura, making AI-based innovations necessary to improve the quality of learning. The objective of this study is to analyze the use of AI-based learning media (ChatGPT, Edpuzzle, and Canva) in supporting ESD in Madura, as well as to examine their impact, challenges, and strategies regarding the improvement of students’ engagement, independence, creativity, and higher-order thinking skills. This study employs a qualitative approach with a descriptive-exploratory design. Data were collected through observation, interviews, and documentation, involving teachers and students as research subjects. Data analysis was conducted using an interactive model encompassing data reduction, data presentation, and drawing conclusions, with validity tested through triangulation of sources and methods. Research findings indicate that the use of ChatGPT can enhance independent learning through adaptive and flexible question-and-answer interactions. The use of Edpuzzle has been shown to increase student engagement and understanding through interactive videos accompanied by evaluative questions. Meanwhile, Canva fosters students’ creativity in producing visual works based on sustainability issues that are contextual to the Madura environment. Furthermore, AI-based learning also contributes to developing students’ critical and reflective thinking skills. However, its implementation still faces challenges such as infrastructure limitations, teacher readiness, as well as ethical and data privacy issues; therefore, optimization strategies are needed through the enhancement of educators’ competencies and sustained policy support.